The Indian inflation–growth relationship revisited: robust evidence from time–frequency analysis - Tiwari, kumar.A; Olayeni, Richard.O; Olofin, Adejonwo.S; Chang, Tsangyao (Taylor and Francis group, 2023)
Taylor and francis, pages;1-18.